PENINGKATAN PRESTASI KERJA PEGAWAIPADA BAGIAN PENYUSUNAN PROGRAM SEKRETARIAT DAERAH KABUPATEN MALINAU KALIMANTAN UTARA - Derafet . (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
This research aims to describe and analyze the work performance of employees, and then to describe and analyze efforts to improve employee performance and to describe factors-factors that support and hinder efforts to improve the work performance of employees in the Division of Program Malinau District Secretariat.The results of the study of employee Achievement in the Program Division of the Secretariat of the Regional District of Malinau in terms of the quality is good enough. While the factors supporting efforts to improve the work performance of employees in the Division of Program Malinau District Secretariat North Kalimantan province are in the form of salary-existence additional fees. While hindering factors are: The low ability of personnel resources, especially in the technical field, less discipline amongst the employee as well as the ineffective utilization of working hours.